Discussion on the mechanism of Danggui Sini decoction in treating diabetic foot based on network pharmacology and molecular docking and verification of the curative effect by meta-analysis - Ni, Xiyu; Bao, Huhe; Guo, Jiaxing; Li, Deer; Wang, Lihang; Zhang, Wanyin; Sun, Guanwen (Frontiers in Endocrinology, 2024)
The main active components and mechanism of Danggui Sini decoction (DSD) in treating diabetic foot (DF) were studied and verified by network pharmacology and molecular docking. Evidence-based medicine was used to prove its efficacy.: The TCMSP systematic pharmacology platform screened out DSD's practical components and targets. Screening disease targets in GeneCards database; Using Cytoscape 3.7.2 to draw DSD-active ingredient-target network diagram; Drawing protein interaction network diagram through STRING database; The Metascape platform is used to analyze GO function enrichment and KEGG signal pathway. The molecular docking experiment was carried out by using Auto Dock vina 4.2. The related literature on DSD in treating DF in China Zhiwang, Wanfang, Weipu, and China Biomedical Literature Database were searched. The literature was screened, data was extracted, and quality was evaluated according to the inclusion and exclusion criteria. Then, a meta-analysis with RevMan 5.3 software. Results: 256 targets of all effective components of DSD were obtained. 1272 disease targets; Among them, there are 113 common targets. GO analysis received 6179 entries; KEGG pathway enrichment analysis found 251 related pathways. The molecular docking results of the main targets of diabetic foot and the active substances of DSD all showed high docking activity. The meta-analysis included 6 literature, all of which were randomized controlled experiments. The quality grade of the literature was C, and the results showed that the total effective rate of clinical efficacy in the experimental group was significantly higher than the control group. Conclusions: DSD may treat DF by participating in biological processes such as cell proliferation regulation, inflammatory reaction, oxidative stress reaction, and promoting angiogenesis. DSD treats DF through AKT1, TP53, IL6, TNF, VEGFA, and other targets. DSD plays a role in treating DF mainly through the AGE-RAGE signaling pathway and PI3K-AKT signaling pathway. The molecular docking results of AKT1, TP53, IL-6, TNF, and VEGFA with the active substances of DSD show that they all have high docking activity; among them, VEGFA has higher docking activity. Compared with conventional treatment, DSD has a high effective rate, short wound healing time, large wound healing area, and high ABI index.